2020
DOI: 10.1007/s41885-020-00077-w
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 with Stigma: Theory and Evidence from Mobility Data

Abstract: This study conducts both theoretical and empirical analyses of how non-legally-binding COVID-19 policies affect people's going-out behavior. The theoretical analysis assumes that under a declared state of emergency, the individual going out suffers psychological costs arising from both the risk of infection and the stigma of going out. Our hypothesis states that under a declared state of emergency people refrain from going out because it entails a strong psychological cost. Then, this study estimates a model u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
68
2
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(84 citation statements)
references
References 30 publications
(23 reference statements)
9
68
2
4
Order By: Relevance
“…According to Yoo and Managi (2020) , the governmental interventions applied to reduce the death cases and promote social distancing may cause a loss of 47.28% of the global annual gross domestic product (GDP). Such results were also achieved, as reported by the findings of recent studies, because “ people who go out under the state of emergency are stigmatized by society as having inferior ethics because they do not follow the social norms ” ( Katafuchi et al., 2020 , p. 3). The transmission mode of the COVID-19 is mainly due to the spread of droplets by infected individuals when coughing or sneezing.…”
Section: Introductionsupporting
confidence: 58%
“…According to Yoo and Managi (2020) , the governmental interventions applied to reduce the death cases and promote social distancing may cause a loss of 47.28% of the global annual gross domestic product (GDP). Such results were also achieved, as reported by the findings of recent studies, because “ people who go out under the state of emergency are stigmatized by society as having inferior ethics because they do not follow the social norms ” ( Katafuchi et al., 2020 , p. 3). The transmission mode of the COVID-19 is mainly due to the spread of droplets by infected individuals when coughing or sneezing.…”
Section: Introductionsupporting
confidence: 58%
“…Further, the analysis showed that both the manufacturing and service sectors are not immune to the COVID-19 effect. This could be explained by the unexpected drop in demand, along with global movement restrictions of products and services in an attempt to curb the spread of the virus ( Katafuchi et al., 2020 ). Moreover, the findings suggest that the global supply chains (both in manufacturing and service sectors) are likely to be vulnerable to such a substantial unexpected disruption, albeit with some differences.…”
Section: Discussion and Implications From The Studymentioning
confidence: 99%
“…The fast and extensive propagation of the novel COVID-19 created immense uncertainties in demands and disruptions in global supply-chains. The pandemic control efforts have interrupted flows of finished goods and raw materials from Chinese factories to many parts of the world, and later from other countries to China along with other destinations, which have had a disastrous impact on the international economy and global supply-chains ( Kumar and Managi, 2020 ; Katafuchi et al., 2020 ).…”
Section: Conclusion and Scope For Further Studiesmentioning
confidence: 99%
“…In the early 2020s, the global health crisis caused by a novel form of coronavirus, named COVID-19 (COrona VIrus Disease 2019), has generated a disruptive impact on most economic and social activities, including schools and universities, people's going-out behavior ( Kurita and Managi, 2020 ; Katafuchi et al., 2020 ). The emergency has forced countries around the world to adopt a variety of policies including social distancing, home quarantine, school closures, and case isolation in order to diminish infections and deaths ( Yoo and Managi, 2020 ).…”
Section: Introductionmentioning
confidence: 99%